Embedded options and the issue of gharar: Malaysian empirical evidence - Haron, Razali (ISTAC, 2015)

(untitled)
Despite its accelerating use in the financial market, embedded options receive contradicting opinions with regards to its permissibility based on the Shariah principles. This study will examine the existence of gharar element in the pricing of an embedded options (warrants), especially in the case of mispricing. The Black Scholes Option Pricing Model (BSOPM), a robust set of methods, is used to analyze the pricing efficiency of warrants market and to detect any mispricing in warrants contracts in Malaysia. Looking from the perspective of informationally efficient market, there seemed to be pricing inefficiency in the local warrants market in reference to their theoretical values. This mispricing of warrants indicated inefficiency in the warrants market and the element of gharar in warrants contract is viewed from the mispricing detected in the study. Mispricing of warrants in Malaysian market indicates speculative activities and speculation is not allowed in Islam. Speculation is prohibited in Islam as it may contain excessive gharar (uncertainty) and maysir (gambling). These may then result in wealth accumulation at the expense of other parties’ jahl (ignorance). This activity violates the concept of adl (justice), does not serve the concept of maslahah (public interest) and does not comply with the Maqasid al Shariah.